2004
DOI: 10.4028/www.scientific.net/kem.264-268.1867
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Properties of the Rare-Earth Doped Glasses

Abstract: RE-Si-Mg-O-N glasses with RE = Sc, Y, La, Yb, Sm, or Lu with two different nitrogen contents were investigated to understand the effects of rare-earth elements and nitrogen on microhardness, indentation modulus, fracture toughness and viscosity. The microhardness and indentation modulus of glasses containing lanthanide dopants increase approximately linearly with the increase of the cationic field strength (CFS) of the corresponding RE element, whereas fracture toughness is almost unaffected. Nitrogen content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 18 publications
2
13
0
1
Order By: Relevance
“…As a result, a glass network containing small lanthanides, such as Lu, has a tighter structure and better properties than the glasses containing lanthanides with greater ionic radii. For instance, the replacement of La by Lu in oxide glasses caused 0022 [21][22][23][24][25].5% and 16-22% increases in YoungÕs modulus in oxide and oxynitride glasses, respectively; hardness increased by 13-16% [17]. Glass transition temperatures in La-glasses without and with 20 eq.% of N were approximately 882 and 960°C, whereas they were $916 and $1010°C in Lu-containing glasses [17].…”
Section: Introductionmentioning
confidence: 97%
“…As a result, a glass network containing small lanthanides, such as Lu, has a tighter structure and better properties than the glasses containing lanthanides with greater ionic radii. For instance, the replacement of La by Lu in oxide glasses caused 0022 [21][22][23][24][25].5% and 16-22% increases in YoungÕs modulus in oxide and oxynitride glasses, respectively; hardness increased by 13-16% [17]. Glass transition temperatures in La-glasses without and with 20 eq.% of N were approximately 882 and 960°C, whereas they were $916 and $1010°C in Lu-containing glasses [17].…”
Section: Introductionmentioning
confidence: 97%
“…23,24 At elevated temperatures, glass transition temperature (T g ) of Y-containing glass fit the dependence while T g of Yb-containing glass was off. 25 Despite unsupported assumptions about possible changes in coordination numbers, the nature of these deviations was unclear. Moreover, the analysis was hampered by possible influence of inhomogeneities and insufficient number of lanthanide dopants in the studied glasses.…”
Section: Introductionmentioning
confidence: 99%
“…This decreasing trend of ceramics is consistent with the dependence of fracture toughness of glasses doped by the RE elements. 27 By this similarity, it can be concluded that in present case the crack most probably propagates within the IGF in reference Si 3 N 4 based ceramics and the toughness of the bulk material is dictated by the properties of glassy phase and not by the strength of the bond between Si 3 N 4 grain and IGF. This fracture, which is dependent on the glassy phase composition, can be one of the reasons for the dissimilarities in the fracture behaviour of samples prepared by Satet et al 1 The knowledge of chemical composition and the structure of the IGF are crucial for this idea.…”
Section: Fracture Toughness Of the Monolithic Si 3 Nmentioning
confidence: 79%